2021
DOI: 10.1186/s12864-020-07310-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of long non-coding RNAs conferring resistance to Colletotrichum gloeosporioides in walnut (Juglans regia)

Abstract: Background Walnut anthracnose caused by Colletotrichum gloeosporioides (Penz.) Penz. and Sacc. is an important walnut production problem in China. Although the long non-coding RNAs (lncRNAs) are important for plant disease resistance, the molecular mechanisms underlying resistance to C. gloeosporioides in walnut remain poorly understood. Results The anthracnose-resistant F26 fruits from the B26 clone and the anthracnose-susceptible F423 fruits from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 67 publications
1
35
0
1
Order By: Relevance
“…The N gene of tobacco ( Nicotiana tabacum ) is a typical R gene engendering the localization of tobacco mosaic virus (TMV) infection and the elicitation of a hypersensitive necrotic response [ 50 ]. In addition, three hub potential R genes (G-type lectin S-receptor-like serine/threonine-protein kinase LECRK1, LOC108979712 ; probably inactive leucine-rich repeat receptor-like protein kinase At2g25790, LOC109009481 ; and TMV resistance protein N-like, LOC108988638 ) obtained in the study of Feng et al [ 29 ] also present in the WGCNA module in this study. Therefore, the roles of these potential R genes in walnut resistance to anthracnose were worth further study.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The N gene of tobacco ( Nicotiana tabacum ) is a typical R gene engendering the localization of tobacco mosaic virus (TMV) infection and the elicitation of a hypersensitive necrotic response [ 50 ]. In addition, three hub potential R genes (G-type lectin S-receptor-like serine/threonine-protein kinase LECRK1, LOC108979712 ; probably inactive leucine-rich repeat receptor-like protein kinase At2g25790, LOC109009481 ; and TMV resistance protein N-like, LOC108988638 ) obtained in the study of Feng et al [ 29 ] also present in the WGCNA module in this study. Therefore, the roles of these potential R genes in walnut resistance to anthracnose were worth further study.…”
Section: Discussionsupporting
confidence: 65%
“…1 c, f, i, l), and distal uninoculated tissues access to the resistance at 120 hpi. Thus, according to the lifestyle transitions of C. gloeosporioides , the resistant fruits (F26) and susceptible fruits (F423) were collected and inoculated according to the description by Feng et al [ 29 ]. The fruit bract tissues of F26 and F423 at 0 hpi, pathological tissues at 24 hpi, 48 hpi, 72 hpi, and distal uninoculated tissues at 120 hpi were used for the transcriptome and proteome analysis.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the expression levels of WRKY in common walnut, 17 transcriptome data were downloaded, including a total of 17 tissues from PJ Martínez-García et al, 2016 (PRJNA291087) [ 51 ], 10 anthracnose-resistant F26 fruits from the B26 clone (AR) and 10 anthracnose-susceptible F423 fruits from the 4–23 clone (AS) of walnut [ 52 ] (PRJNA612972) ( Table S1 ). Cufflinks was used to [ 53 ] to quantify these gene expression levels based on fragments per million base readings per million mapped read (FPKM) values with default parameters, and expression level was calculated using Hemi 1.0 software with default parameters [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genes related to the salicylic acid-mediated defence process were co-expressed with lncRNAs in kiwifruit plant challenged with the bacteria P. syringae . Likewise, lncRNAs of resistant walnuts to C. gloeosporioides were predicted to trans-regulate genes involved in defence pathways of the jasmonic acid and auxins (Feng et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In kiwifruit leaves infected by P. syringae, a weighted gene co-expression network analysis revealed a number of lncRNAs closely related to plant immune response and signal transduction . Likewise, Feng et al (2021) identified 14,525 lncRNAs related to the walnut anthracnose resistance. This analysis showed that the target genes of the up-regulated lncRNAs were enriched in immune-related processes during the infection of the causal agent Colletotrichum gloeosporioides.…”
Section: Introductionmentioning
confidence: 99%